Análisis socioeconómico de los comerciantes informales de marisco del Cantón Buena Fe, Provincia de Los Ríos, 2016. - López Alarcón, Vicente Gerónimo (2016)
The study carried out on the basis of a Socioeconomic Analysis of informal seafood merchants in the Canton of Buena Fe, was carried out in order to identify the factors that encompass economic, cultural and social growth, economic activity. A well-developed analysis requires a series of resources that allowed the objectives to be achieved, including the study of the economic, social, cultural and political aspects of the informal merchants dedicated to the sale of shellfish, thus being able to know their level of Life (economic situation), who are the people involved in the distribution and marketing of seafood, having thus determined who are their current customers (retail or human consumption) and potential (restaurants or other type of commerce) and its main suppliers (Wholesale intermediaries and fishermen). It is vital in a research to use techniques and tactics with the aim of obtaining real and concise information, it is in such a way that the tools that were used were the surveys and direct observation, which helped to obtain satisfactory results because they identified aspects before Considered relevant and today play a supportive role within an economy, the methods used in this study were inductive and deductive methods. Through the research carried out, we can find shortcomings that in turn served to reinforce the socioeconomic aspects by providing guidelines that allow them to have higher incomes, which in turn allows them to have a better quality of life in the not too distant future. Emphasis is given to people engaged in seafood marketing to avoid buying middlemen a bit as they take a percentage of their profits.